A method for detection and differentiation of Mycoplasma gallispeticum. - Ideris, Aini; Omar, Abdul Rahman; Bejo, Mohd Hair; Tan, Ching Giap; Liew, Pit Sze (2010)

(untitled)
The present invention provides a method of simultaneously detecting and differentiating Mycoplasma gallisepticum strains that cause respiratory infections in avian species. The method includes providing a nucleic acid prepared from a suspected biological sample, amplifying the nucleic acid with amplification primers specific for target genomic regions of Mycoplasma gallisepticum, and detecting the amplification products. The invention also relates to a diagnostic kit for carrying out the inventive method.